CEMARAN MIKROBIOLOGIS JUS ALPUKAT YANG DIJUAL DI JALANAN KOTA SURAKARTA - Beti Cahyaning Astuti; Eko Yuliastuti; Akhmad Mustofa; Ainun Mardiyah; Nanik Suhartatik (AGROINTEK, 2020)
Fresh fruit juice was processed food was a part of healthy diet. Daily fresh juice consumption could improve health and prevent the occurrence of degenerative disease. Fresh juice were produce without any heat treatment which could allow natural microflora to growth. The aims of the research was to determine the microbiological contaminant of avocado street juice sold in Surakarta. Twenty five of samples were taken from 5 district. Samples were analyze for total viable aerobic count (TVAC), total coliform, total salmonella count, and total staphylococci. The results showed that microbiological contaminant of street avocado juice was extremely high. TVAC of avocado juice was 6.07 ± 0.37 to 8.95 ± 0.04 log CFU/ml; Total coliform 3.28 ± 0.01 to 4,60 ± 0,02 log CFU/ml; Total Staphylococci 4,47 ± 0,07 to 7,35 ± 0,07 log CFU/ml; and Total Salmonella-Shigella 2,34 ± 0,06 to 4,80 ± 0,00 log CFU/ml. There was 1 grocery that produce avocado juice which have undetected for coliform analysis. Producers, government and also consumers need to make some agreement to improve the safety of fresh juice.